Decision Support Systems For Teacher Performance Evaluation at SDI Darul Mu’minin With Analytical Hierarchy Process And Simple Additive Weighting Methods: Sistem Pendukung Keputusan Evaluasi Kinerja Guru di SDI Darul Mu’minin Dengan Proses Hierarki Analitik Dan Metode Additive Weighting Sederhana - Dwi Setyo Aji; Anita Diana; Atik Ariesta; Grace Gata; Dwi Achadiani (SYSTEMATICS, 2023)
Teacher performance evaluation is one of the efforts to raise the standard of education at SDI Darul Mu'minin. SDI Darul Mu'minin, which is located in Larangan Indah Village, Larangan sub-district, Tangerang City, has a teacher performance assessment that is conducted once a year. In addition to raise the standard of education, the purpose of the assessment is to select exemplary teachers. However, the process of assessing teacher performance is not on target because the assessment process only uses attendance criteria and does not yet have the right method. Therefore the principal added several additional criteria, namely: responsibility, lesson plans, loyalty and reporting of student grades. To implement a multi-criteria assessment, a decision support system is needed. This study uses the AHP and SAW methods and produces weights namely Responsibility 33%, Loyalty 28%, Attendance 18%, Lesson Plans 13% and Reporting of Student Values ​​8% and produces the best alternative, namely the best performing teacher with a value of 0.9930. The goal of this research is to decide the best alternative, namely the best performing teacher who will receive a prize or reward in the form of money at the end of each academic year.